Indivíduo, propriedade privada e Psicologia Crítica: contribuições marxistas para a crítica da Psicologia e do capitalismo - Mesquita, Tamara de Castro Mendonça (2020)
The study at issue aimed to carry out a bibliographic survey about the presence of a debate on private property in the scope of Psychology, especially in the field referred to as Critical Psychology. Based on the understanding that this strand reunites trends that criticize society and the traditional perspectives of the discipline, it was considered necessary to highlight the importance of a criticism that takes property into account, since this is a central category both in the structure of the current society and in the model of individual abstracted by Psychology. Therefore, here is presented an analysis of the main thematic fields in which references to property were found in the literature in Psychology available online, especially those that sought to identify the cathegory as a structuring of capitalism and, thus, could enroll themselves in a perspective of social transformation. Once a gap was found around this debate in the texts found, and/or not very in-depth conceptions about the topic of property, marxists contributions were raised to situate the category in the process of human self-constitution, aiming to understand its historical movement and its consequences in the realization of the potentialities that are placed on the horizon of the individual and gender. The relationship of mutual determination between private property and alienation was analyzed, along the different modes of production, mainly the implications that it puts to the division of labor and the possibility of the individual's existence as an active entity in history. As a conclusion, the argument presented is that, in different formats, the existence of property has always dragged with itself relations of exploitation and violence, which are restored under new configurations and reiterate a mode of alienated sociability. In this respect, this study sought to make theoretical-practical considerations that align Critical Psychology with the construction of an ethical-political project that seeks suprasumption of property and its consequences, since a position that locates discipline in the class struggle